The Effects of Workload, Job Insecurity, and Supervisor Support on Work-Life Balance Among Telemarketing Agents at A Private Retail Company, with Job Stress as A Mediating Variable - Athalia Tiffany; Nia Kusuma W (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Work-life balance has become a critical concern in high-pressure service sectors, particularly among telemarketing agents who face demanding performance targets, rotating work shifts, and precarious employment arrangements that blur the boundaries between work and personal life. This study aimed to examine the effects of workload, job insecurity, and supervisor support on work-life balance among telemarketing agents at a private retail company, with job stress serving as a mediating variable. The study population consisted of all telemarketing agents employed by the company (N = 99), and the entire population was included using a saturated (census) sampling technique. Data were collected through an online questionnaire administered via Google Forms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicated that workload and job insecurity had positive and significant effects on job stress, whereas supervisor support did not have a significant effect on job stress. Furthermore, job stress had a significant effect on work-life balance, whereas workload, job insecurity, and supervisor support did not have significant direct effects on work-life balance. In addition, job stress significantly mediated the relationships between workload and work-life balance and between job insecurity and work-life balance. However, job stress did not significantly mediate the relationship between supervisor support and work-life balance. These findings indicate that job stress serves as the primary psychological mechanism through which job demands contribute to work-life imbalance among telemarketing agents.